Digitalisasi Surat Tugas dan Perjalanan Dinas KPU Provinsi Jawa Timur Berbasis Website dengan Metode Prototype - Septiana, Rochmah Septiana; M. Andik Izzuddin; Ilham Ilham (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to address administrative inefficiencies within the East Java Provincial General Elections Commission (KPU) in the issuance process of Assignment Letters (ST) and Official Travel Letters (SPD), which have been managed manually using separate documents. Such a process often leads to delays, data duplication, and input errors. To overcome these issues, this research designed and implemented a web-based information system called SimpelTugas (Simple Task Management System) to digitalize and integrate the workflow. The system was developed using the prototype method, allowing close interaction between developers and users to ensure alignment with KPU’s administrative procedures. The main features of SimpelTugas include digital verification, integration of ST and SPD data, and automatic document numbering, all of which replace previously manual tasks. The implementation results show that the system significantly improves administrative efficiency, reduces errors, accelerates document validation, and enhances transparency in official travel reporting. Consequently, the adoption of SimpelTugas represents a strategic step toward institutional digital transformation and the modernization of administrative governance within the East Java Provincial KPU.